Brucella seroprevalence in cattle near a wildlife reserve in Kenya. (December 2017) - Enström, Sofie; Nthiwa, Daniel; Bett, Bernard; Karlsson, Amanda; Alonso, Silvia; Lindahl, Johanna
Abstract Objectives Brucellosis is caused by bacteria from the genusBrucella which infect human and domestic animals as well as wildlife. The Maasai Mara National Reserve has vast populations of wild ruminants such as buffaloes and wildebeest which could contribute to the risk of brucellosis in livestock, and the surrounding pastoralist communities grazing cattle in and around the reserve may be exposed to a higher risk of zoonotic diseases like brucellosis due to the close contact with livestock. In this study, cattle from three villages at varying distance from the reserve, were screened for antibodies againstBrucella abortus . Results In total, 12.44% of 225 sampled animals were seropositive, with more females (15%) infected than males (5%). Seroprevalence was higher in livestock closer to Maasai Mara with the cattle in the village Mara Rianta having an odds ratio of 7.03 compared to Endoinyo Narasha further away (95% CI 1.4–11.1, p = 0.003), suggesting that a closer contact with wildlife may increase the circulation of infectious diseases between livestock and wildlife. Symptoms consistent with brucellosis were reported to occur in both humans and animals, and we thus conclude that brucellosis may be an important problem, both for the health and the economy.